2017
DOI: 10.3389/fpls.2017.00203
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Polyamines, Abscisic Acid, Nitric Oxide, and Hydrogen Peroxide under Chilling Stress in Tomato (Lycopersicon esculentum Mill.) Seedlings

Abstract: Polyamines (PAs) play a vital role in the responses of higher plants to abiotic stresses. However, only a limited number of studies have examined the interplay between PAs and signal molecules. The aim of this study was to elucidate the cross-talk among PAs, abscisic acid (ABA), nitric oxide (NO), and hydrogen peroxide (H2O2) under chilling stress conditions using tomato seedlings [(Lycopersicon esculentum Mill.) cv. Moneymaker]. The study showed that during chilling stress (4°C; 0, 12, and 24 h), the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 93 publications
(131 reference statements)
4
58
0
2
Order By: Relevance
“…However, there were no difference between the control and high‐temperature treatment. NR activity and increased expression under chilling stress has been reported earlier . Ferredoxin‐thioredoxin system is one of the major regulations of chloroplast enzyme activity and a response to various stress conditions…”
Section: Discussionsupporting
confidence: 54%
“…However, there were no difference between the control and high‐temperature treatment. NR activity and increased expression under chilling stress has been reported earlier . Ferredoxin‐thioredoxin system is one of the major regulations of chloroplast enzyme activity and a response to various stress conditions…”
Section: Discussionsupporting
confidence: 54%
“…Exposure to low temperature induces oxidative and nitrosative stress thereby promoting NO synthesis [119], which serves as a potential link between PA and ABA to induce stress responses in plants [120]. Literature indicated extensive cross talk among NO, ABA, PAs, and H 2 O 2 to modulate various physiological and stress responses under low temperature conditions [110,121]. Interplay among NO, SA, and ABA was noted to enhance the antioxidative activities (CAT, SOD, POX) that contributed to improved chilling injury in Zea mays seedlings [122].…”
Section: No-phytohormone Cross Talk Under Temperature Stressmentioning
confidence: 99%
“…LeADC1), and ornithine decarboxylase (LeODC) to improve chilling stress tolerance in Lycopersicon esculentum leaves. However, the expression of genes encoding Spm synthase (LeSPMS) and S-adenosylmethionine decarboxylase (LeSAMDC) was not inluenced by NO treatment [121]. Reports of Li et al [124] showed that NO treatment converts Put into Spd or Spm to confer cold tolerance in Zingiber oicinale seedlings.…”
Section: No-phytohormone Cross Talk Under Temperature Stressmentioning
confidence: 99%
“…NO production can also be inhibited by the application of N ‐nitro‐ l ‐Arg‐methyl ester ( l ‐NAME), an NOS‐like inhibitor in plants . It is also likely that polyamines mediate NO production …”
Section: Introductionmentioning
confidence: 99%
“…8 It is also likely that polyamines mediate NO production. 9,10 Abscisic acid (ABA) is a sesquiterpenoid and a signal molecule that is important in plant tolerance to stress factors. 11 ABA can be synthesized by a direct pathway in fungi and by an indirect pathway in plants.…”
Section: Introductionmentioning
confidence: 99%